DESKRIPSI KITAB SENJATA MUKMIN DAN RISALAH DOA - Muhammad Adriani Yulizar; Hamidi Ilhami (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2014)
This article describes the work of K.H. Husin Qadri and K.H. Ja'far Sabran; twoproductive scholarswho wrote manyreligious literatures related to monotheism, sharia, morals, deedsand prayers.  K.H. Husin Kadri,a famous writer in his time, had  a brilliant idea to write  a book contained of  collection of prayers al-Ma'sturat  from Al-Quran and Hadith.  Althoughhe did not include the references of  prayers and quotation used in his book,  the Book ofSenjata Mukmin was devotedto students community and Martapura residents  who have understood, and memorizedthe verses or hadith  in that book.  K.H. Husin Kadri  also included  a material of monotheism  which described the explanation of  twentycharacteristics.  The Book of Risalah Doawas composedwithmodel and format designed by the editors to make it different from other people's work, accompanied by interesting information quoted from credible sources. This book was completed withnumber of verses and chapters, the source of hadith’squotations and sayings  of scholarsfrom other books.